2023
DOI: 10.3390/horticulturae9020164
|View full text |Cite
|
Sign up to set email alerts
|

Organo Mineral Fertilizers Increases Vegetative Growth and Yield and Quality Parameters of Pomegranate cv. Wonderful Fruits

Abstract: In recent years, to improve sustainable production in horticultural crops, many new types of strategies have been developed, including organo-mineral fertilization to complement chemical fertilizers in order to enhance the nutritional status of plants and sustainability of the agroecosystems. This study was performed on a young pomegranate orchard of the “Wonderful” cultivar during the 2018 and 2019 seasons. The purpose was to evaluate the effects of three foliar applications (at the red ball, fruit setting, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
1
4
1
Order By: Relevance
“…Similarly to our study, increases in fruit color index with the use of biostimulants have been reported in apples (43,44) and grapes [45], which may be due to the ability of biostimulants to modulate the activity of endogenous hormones, resulting in the induction of color biosynthesis pathways in the skin of the fruit (46, 47). Conversely, the results of the current study are contrary to those obtained by Tarantino et al [48,49] on apricots and Tarantino et al [50] on pomegranates, which showed no effect of biostimulants on the fruit color index. Furthermore, our results support those achieved by Abidi et al [51] on peaches and nectarines, showing that the application of potassium silicate enhanced the color indices of fruits.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Similarly to our study, increases in fruit color index with the use of biostimulants have been reported in apples (43,44) and grapes [45], which may be due to the ability of biostimulants to modulate the activity of endogenous hormones, resulting in the induction of color biosynthesis pathways in the skin of the fruit (46, 47). Conversely, the results of the current study are contrary to those obtained by Tarantino et al [48,49] on apricots and Tarantino et al [50] on pomegranates, which showed no effect of biostimulants on the fruit color index. Furthermore, our results support those achieved by Abidi et al [51] on peaches and nectarines, showing that the application of potassium silicate enhanced the color indices of fruits.…”
Section: Discussioncontrasting
confidence: 99%
“…Similar to our ndings, increases in fruit antioxidant activity with the use of biostimulants have been reported in tomatoes [63, 68], apples [43,47], and apricots [48]. However, the results of this study are contrary to those obtained by Tarantino et al [49] on apricots and Tarantino et al [50] on pomegranates, who reported that the use of biostimulants does not cause any change in the antioxidant activity of fruits.…”
Section: Discussionsupporting
confidence: 85%
“…Pomegranate products, including juice, wine, vinegar, and others, are widely accepted by consumers globally (Kalaycıoglu and Erim, 2017). Pomegranate juice, constituting 78% (w/w) (Singh et al, 2022) of fresh food products, exhibits three times higher antioxidant activity compared to wine and green tea (Arantino et al, 2023). In this study, the TPC, TFC and TMAC of 'Tunisia' and 'Qingpi' fruit juice were respectively 0.53-2.95 mg GAE/g, 0.84-2.55 mg RE/g, and 2.67-208.35 nmol/g, which were lower than 'Wonderful' pomegranate juice (Arantino et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate juice, constituting 78% (w/w) (Singh et al, 2022) of fresh food products, exhibits three times higher antioxidant activity compared to wine and green tea (Arantino et al, 2023). In this study, the TPC, TFC and TMAC of 'Tunisia' and 'Qingpi' fruit juice were respectively 0.53-2.95 mg GAE/g, 0.84-2.55 mg RE/g, and 2.67-208.35 nmol/g, which were lower than 'Wonderful' pomegranate juice (Arantino et al, 2023). El Kar et al (2011 reported TPC, TFC, and TMAC in juice of 'Tunisia' and 'Gabsi' as 458-3299 mg GAE/L, 135-636 mg QE/L, and 11-178 mg CGE/L, respectively, and their ranges were also higher than those in this experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Pomegranate products, including juice, wine, vinegar, and others, are widely accepted by consumers globally (Kalaycıoglu and Erim, 2017). Pomegranate juice, constituting 78% (w/w) (Singh et al, 2022) of fresh food products, exhibits three times higher antioxidant activity compared to wine and green tea (Arantino et al, 2023). In this study, the TPC, TFC and TMAC of 'Tunisia' and 'Qingpi' fruit juice were respectively 0.53-2.95 mg GAE/g, 0.84-2.55 mg RE/g, and 2.67-208.35 nmol/g, which were lower than 'Wonderful' pomegranate juice (Arantino et al, 2023).…”
Section: A B D C Figurementioning
confidence: 99%